1997
DOI: 10.1098/rspa.1997.0097
|View full text |Cite
|
Sign up to set email alerts
|

The effects of freestream pressure gradient on a corner boundary layer

Abstract: The incompressible boundary layer in the corner formed by two intersecting perpendicular semi-infinite planes is investigated; the freestream flow, aligned with the corner, is of the form x * n , x * representing the streamwise distance from the leading edge. Similarity-type asymptotic solutions for large Reynolds numbers are derived and it is found that solutions do not exist for all values of the parameter n, and that for values of n where solutions do exist, non-uniqueness is a common feature; previous theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 20 publications
3
41
0
Order By: Relevance
“…In seeking solutions to corner boundary-layer problems, Ridha (1992) and Dhanak & Duck (1997) found that if a cross-flow component of flow is permitted, which grows linearly in the cross-flow direction (the other two velocity components are independent of this distance), then two distinct solution branches are obtained. A corollary which arises from this work is that the (two-dimensional) Blasius solution has a three-dimensional alternative, which possesses a jet-like cross-flow velocity component.…”
Section: Introductionmentioning
confidence: 99%
“…In seeking solutions to corner boundary-layer problems, Ridha (1992) and Dhanak & Duck (1997) found that if a cross-flow component of flow is permitted, which grows linearly in the cross-flow direction (the other two velocity components are independent of this distance), then two distinct solution branches are obtained. A corollary which arises from this work is that the (two-dimensional) Blasius solution has a three-dimensional alternative, which possesses a jet-like cross-flow velocity component.…”
Section: Introductionmentioning
confidence: 99%
“…Despite being somewhat less intuitive than the primitive variable formulation, this form of (1) is well known in relation to corner boundary-layer flows, see for example the formulation of Dhanak and Duck [15] or Pal and Rubin [16]. We will follow the formulation of [15] further by combining (5a) and (5b) to obtain expressions for the Laplacian of both Φ and Ψ given by…”
Section: Formulationmentioning
confidence: 99%
“…where φ = O(1) in order to match with the spanwise varying displacement induced by the parabolic solution (15) and ζ 0η + δ F is the (outer) η → ∞ limit of the (inner) Falkner-Skan solution. Rewriting (5a) and (5b) in terms of ζ andη, and since both U and Θ remain o(ζ −2 0 ), we find that φ is determined by the harmonic problem,…”
Section: Asymptotic Description For ζ 0 → ∞: the Macro-scale Slot Limitmentioning
confidence: 99%
“…This approach assumes that spanwise lengthscales are comparable to the transverse boundarylayer thickness, ensuring that diffusion in the cross section is retained in both directions, but the longer streamwise lengthscale leads to neglect of streamwise diffusion. Similar formulations have previously been employed in high Reynolds number descriptions of (for example) corner boundary regions (Dhanak & Duck 1997), wakes behind elongated roughness elements (Goldstein et al 2016), flow near small-scale surface gaps (Hewitt & Duck 2014), the influence of upstream vorticity on transition (Wundrow & Goldstein 2001) and the generation of laminar streaks by freestream vorticity (Ricco & Dilib 2010). The formulation of van Dommelen & Yapalparvi (2014) is also equivalent if one considers the zero-curvature limit of their equations, although in their case the short-scale spanwise forcing is also assumed to be periodic, which simplifies the far-field behaviour compared to the (finite-spanwise extent) our problem.…”
Section: Introductionmentioning
confidence: 99%